ANALYSIS OF DIGITAL TRANSFORMATION AS A DRIVER OF WORKFORCE AGILITY: A SYSTEMATIC REVIEW FROM A TALENT MANAGEMENT PERSPECTIVE - Heriyanto; Fiona Niska Dinda Nadia; Elisabeth Supriharyanti (CV. Radja Publika, 2026)
Digital transformation has become a strategic necessity for organizations, enhancing competitiveness in the modern economy. While extensive Research explores technological and operational aspects, understanding how digital initiatives affect workforce agility through talent management remains limited. This systematic literature review examined 19 peer-reviewed articles (2021-2025) to explore how digital transformation enhances workforce agility and how talent management strengthens this relationship. Following the PRISMA framework and PICO criteria, we systematically searched four databases (SagePub, Scopus, ScienceDirect, Wiley) and managed articles using Covidence for quality screening. Analysis revealed three main pathways: First, digital transformation enhances workforce agility by developing digital capabilities and adopting innovation. Second, strategic talent management practices mediate relationship between digital initiatives and workforce agility outcomes. Third, organizational factors like leadership, culture, and HR analytics moderate the strength of these relationships. Significant Research gaps emerged, including limited examination of age diversity in digital talent management, insufficient understanding of implementation barriers in developing countries, and a lack of longitudinal evidence on the sustainability of workforce agility. This study proposes an integrated framework that combines perspectives on digital transformation, workforce agility, and talent management, advancing theoretical understanding and providing practical insights for HR professionals navigating organizational change amid complex digitalization processes.